2010
DOI: 10.1016/j.otsr.2010.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Braun's flexor tendons transfer in disabled hands by central nervous system lesions

Abstract: Our easy-to-use system for evaluating the nonfunctional hand (MHS) was shown to be very effective in demonstrating the improvement of the postoperative result. The originality of our series was to show that Braun's original operation goals were only exceptionally and remotely achieved and that an additional technical procedure must be nearly systematically considered. All the patients in our series were followed up in multidisciplinary team visits where the patient's family and caretakers were encouraged to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Many articles suggest tendon transfer to enhance function or to ease the care in spastic hands. Transfer of the FDS tendon to the FDP is one of the most common techniques (38)(39)(40)(41). Keenan et al (38) reported full accomplishment of goals after the procedure in 34 clenched-fist which were hand open position with the resolution of hygienic problems of palmar skin.…”
Section: Wrist and Fingermentioning
confidence: 99%
“…Many articles suggest tendon transfer to enhance function or to ease the care in spastic hands. Transfer of the FDS tendon to the FDP is one of the most common techniques (38)(39)(40)(41). Keenan et al (38) reported full accomplishment of goals after the procedure in 34 clenched-fist which were hand open position with the resolution of hygienic problems of palmar skin.…”
Section: Wrist and Fingermentioning
confidence: 99%
“…Surgical procedures for the non-functional spastic upper limb have been shown to be effective in the longer term (Heijnen et al., 2008; Keenan et al., 1987; Pomerance and Keenan, 1996). Past publications have reviewed improvement in function and hygiene, or measured opening of the fingers (Facca et al., 2010; House et al., 1981; Keenan et al., 1987; Thevenin-Lemoine et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…STP transfer must frequently be combined with wrist flexor elongation and arthrodesis [17,27] or peripheral neurectomies [25,27] to improve deformity correction.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 22 reviewed studies, 19 (86.36%) provided level III evidence, and 21 (95.45%) obtained a low or very low score on the GRADE scale (Table 3) [39,40] (Figure 2). Sixteen studies were retrospective case series [12,17,18,[21][22][23][24][26][27][28][29][30][31][32][33]37], two were single-center [25] or multi-center [38] retrospective cohort studies, three were prospective case series [34][35][36], and one was a randomized controlled trial [16]. Only three studies included a comparative group, formed by patients who were treated with rehabilitation in two [16,38] and those undergoing a different surgical technique in the third [25].…”
Section: Quality Of Evidencementioning
confidence: 99%
See 1 more Smart Citation